Yoga, emotion, and behaviour: becoming conscious of habitual social roles - Bastos, Cecilia (Journal of Contemporary Religion, 2024)
This article demonstrates how yoga practitioners seek to attain mental balance by the constant discipline of being aware of their thoughts and actions, learning to react to emotions and desires. It focuses on the efforts it takes to achieve this mental state and the meanings attributed to the cessation of practitioners’ ‘most natural’ way of thinking and feeling. By acknowledging the adherence to norms and values of the learned yoga traditions, this article presents the tensions involved in their identity construction, for this adherence points to a contradiction at a time when it is important to ‘find oneself’ and to live according to one’s own parameters. Therefore, the article concludes that the embodiment of a life of yoga does not consist solely in the performance of certain attitudes and behaviours. While there is an attempt to attain integration of body and mind, practitioners of yoga and meditation strive to become aware of habitual social roles and, when conscious of the processes of building a self-image, they make use of these practices as a means to relativise this construction.
Created from Fastlane, Scopus look-up
Keywords: Behaviour; body; emotion; identity; tradition; yoga